Georg Simmel and the “Relational Turn”. Contributions to the foundation of the Lebenssoziologie since Simmel - Ruggieri, Davide (Simmel Studies, 2017)
The first aim of the paper is an interpretation of Georg Simmel’s sociology in “relational terms” – i.e., under the categories of the “relational sociology”; it focuses, thus, to show how Simmel’s social theory and philosophy of culture fit for the construction of a Lebensoziologie. Considering Simmel as a “relational sociologist” means to demonstrate how his contribution is decisive to the history of sociology, since he defines the “Wechselwirkung” (reciprocity, relational exchange) and its forms as the very matter of the social sciences. Simmel represents the “relational turn” in the wide sociological milieu. Since Simmel’s contribution, sociology attempted to consider and investigate social facts in terms of “relation” and reciprocity. The current sociological debate insists on considering Simmel as a “relational” sociologist in various declinations (coherent to Bourdieu’s social theory or to the social network analysis framework). In his late essays and books Simmel gives a “vitalist” accent to the analysis of social facts: the social is above all “social life”, according to the consolidated forms/contents dialectical model. Grundfragen der Soziologie. Individuum und Gesellschaft represents his last attempt to corroborate a sort of “sociology of life” (Lebenssoziologie). Even if this term does not explicitly appear in Simmel’s words, it summarizes his social and cultural theory - since the volume Soziologie - and offers some key-concepts for the successive sociological debate.